Simultaneously incorporating atomically dispersed Co-Nx sites with graphitic carbon layer-wrapped Co9S8 nanoparticles for oxygen reduction in acidic electrolyte - Wu,J; Gong,M; Zhang,W; Mehmood,A; Zhang,J; Ali,G; Kucernak,A (ChemElectroChem, 2023)
A facile yet robust synthesis is reported herein to simultaneously incorporate atomically dispersed Co-Nx sites with graphitic layer-protected Co9S8 nanoparticles (denoted as Co SACs+Co9S8) as an efficient electrocatalyst for oxygen reduction in acidic solution. The Co SACs+Co9S8 catalyst shows low H2O2 selectivity (∼5 %) with high half-wave potential (E1/2) of ∼0.78VRHE in 0.5M H2SO4. The atomic sites of the catalyst were quantified by a nitrite stripping method and the corresponding site density of the catalyst is calculated to be 3.2×1018sites g−1. Besides, we also found the presence of a reasonable amount of Co9S8 nanoparticles is beneficial for the oxygen electrocatalysis. Finally, the catalyst was assembled into a membrane electrode assembly (MEA) for evaluating its performance under more practical conditions in proton exchange membrane fuel cell (PEMFC) system.